12-Year Compulsory Learning Program In Grade Vii Through Citizenship Project In PPKn Subject At State Middle School 49 Surabaya - Adhistyananda, I Komang Raditya; Nurul Izzah, Oksiana Jatiningsih Naqiya (WAHANA, 2026)
This study aimed to analyze the implementation of Citizenship Project-based learning in PPKn subjects to support the 12-year compulsory education program at SMP Negeri 49 Surabaya. The study employed Classroom Action Research (CAR) involving 33 students of class VIII-B. The research was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. Data were collected through classroom observations, student participation assessments, reflective notes, and project performance rubrics. The findings showed that the Citizenship Project improved students’ critical thinking, participation, collaboration, and argumentative skills. Student participation increased from 65 percent in Cycle I to 87 percent in Cycle II. In addition, students demonstrated greater confidence in expressing opinions and solving social issues related to education and citizenship. The implementation of project-based civic learning also strengthened students’ understanding of democratic values and social responsibility. Therefore, the Citizenship Project can serve as an innovative learning model in PPKn to support active, democratic, and meaningful learning aligned with the goals of the 12-year compulsory education program.